The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11930-017-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Health Care in the U.S. Military and Veterans Health Administration Facilities

Abstract: Purpose of the Review Health care for transgender veterans in the United States (U.S.) Veterans Health Administration (VHA) is relatively new and for active duty service members (ADSMs) in the military is quite recent. Prevalence of transgender veterans and ADSMs, health conditions, and healthcare provision in VHA and military facilities are reviewed. Recent Findings There are approximately 134,300 transgender veterans and 15,000 ADSMs. Based on diagnostic codes, more than 5000 transgender veterans receive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Prior studies have found race to have an association with housing instability. For example, a study found higher rates of housing instability among black trans women compared to their white trans peers [3,41]. Prior studies found housing instability to be associated with social stigmatization for being transgender, but we did not identify literature showing associations between housing instability and intersectional, or combined anti-trans and racial discrimination [8,13].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Prior studies have found race to have an association with housing instability. For example, a study found higher rates of housing instability among black trans women compared to their white trans peers [3,41]. Prior studies found housing instability to be associated with social stigmatization for being transgender, but we did not identify literature showing associations between housing instability and intersectional, or combined anti-trans and racial discrimination [8,13].…”
Section: Discussionmentioning
confidence: 87%
“…Trans women have a higher likelihood of unmet basic needs than the general population, such as inadequate food and housing, which have in turn been associated with poor health outcomes [1,2,3]. A study in Los Angeles ( n = 517) that analyzed the relationship between hormone use and structural inequities (income, housing, and health insurance) among trans women found that more than half of study participants were unstably housed, 22.4% were marginally housed, and 34.8% were homeless [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those who are no longer serving, higher rates of utilization may relate to the rapidly expanding availability of VHA services over the past decade for veterans who identify as TGD (31). Veterans who identify as TGD have reported being treated respectfully by VHA providers and have described being highly satisfied with their care (27,32).…”
Section: Discussionmentioning
confidence: 99%
“…There are currently 134,300 transgender veterans and an estimated 15,000 transgender Americans in active military service [43], so appropriate transgender care is especially critical for these populations [35,36,[42][43][44].…”
Section: Barriers To Gender-affirming Surgerymentioning
confidence: 99%